Genome-edited HEADING DATE 3a knockout enhances leaf production in Perilla frutescens - Yun, Hee Rang; Chen, Chong; Kim, Jee Hye; Kim, Hae Eun; Karthik, Sivabalan; Kim, Hye Jeong; Chung, Young-Soo; Baek, Hee Soon; Sung, Sibum; Kim, Hyun Uk; Heo, Jae Bok (Frontiers in Plant Science, 2023)
Environmental cues regulate the transition of many plants from vegetative to flowering development. Day length, or photoperiod, is one cue that synchronizes flowering by changing seasons. Consequently, the molecular mechanism of flowering control is prominent in Arabidopsis and rice, where essential genes like FLOWERING LOCUS T (FT) homolog, HEADING DATE 3a (Hd3a), have been connected to flowering regulation. Perilla is a nutrient-rich leaf vegetable, and the flowering mechanism remains largely elusive. We identified flowering-related genes under short-day conditions using RNA sequencing to develop an enhanced leaf production trait using the flowering mechanism in the perilla. Initially, an Hd3a-like gene was cloned from the perilla and defined as PfHd3a. Furthermore, PfHd3a is highly rhythmically expressed in mature leaves under short-day and long-day conditions. Ectopic expression of PfHd3a in Atft-1 mutant plants has been shown to complement Arabidopsis FT function, resulting in early flowering. In addition, our genetic approaches revealed that overexpression of PfHd3a in perilla caused early flowering. In contrast, the CRISPR/Cas9 generated PfHd3a-mutant perilla showed significantly late flowering, resulting in approximately 50% leaf production enhancement compared to the control. Our results suggest that PfHd3a plays a vital role in regulating flowering in the perilla and is a potential target for molecular breeding in the perilla.